2016
DOI: 10.15666/aeer/1402_265281
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Occlusion Potential of Rice Phytoliths: Implications for Global Carbon Cycle and Climate Change Mitigation

Abstract: Abstract. Phytoliths are silica bodies produced by plants through bio-mineralization process. During such process, occlusion of carbon (C) also takes place within the phytoliths called phytolith occluded C (PhytOC). The PhyOC is highly stable and may substantially contribute to long-term terrestrial C sequestration. The present study aimed to investigate the phytolith and PhytOC contents variability in rice cultivars and its potential for long-term terrestial C biosequestration.The results indicate that dry ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 33 publications
0
7
0
Order By: Relevance
“…There was a significant correlation between the Si content and the phytolith content of the crop materials, such as the phytolith contents of the rice leaves, stems and sheaths (Song et al, 2014a). The shape of the phytoliths in the different rice organs varied (e.g., double-peaked, bulliform, and parallel dumbbell phytoliths) (Prajapati et al, 2016). Prajapati et al (2016) reported that the phytolith content in the different rice organs (stem, sheath, leaf, and grain) ranged from 0.14 to 26.4 g kg -1 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…There was a significant correlation between the Si content and the phytolith content of the crop materials, such as the phytolith contents of the rice leaves, stems and sheaths (Song et al, 2014a). The shape of the phytoliths in the different rice organs varied (e.g., double-peaked, bulliform, and parallel dumbbell phytoliths) (Prajapati et al, 2016). Prajapati et al (2016) reported that the phytolith content in the different rice organs (stem, sheath, leaf, and grain) ranged from 0.14 to 26.4 g kg -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The shape of the phytoliths in the different rice organs varied (e.g., double-peaked, bulliform, and parallel dumbbell phytoliths) (Prajapati et al, 2016). Prajapati et al (2016) reported that the phytolith content in the different rice organs (stem, sheath, leaf, and grain) ranged from 0.14 to 26.4 g kg -1 . Similar results and trends were reported by other researchers (Li et al, 2013c; Guo et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Phytolith makes up from 1.6 to 14.4% of rice (stem, sheath, and leaf) 9,22 , thereby hundreds of million tonnes of phytolith are recycled annually if all world rice residues are returned to the soil instead of exported or used for other purposes. Phytoliths, including fresh phytolith (from straw residue incorporated into soil), ash phytolith (obtained from straw burning) and aged phytoliths (both fresh and ash phytoliths buried in soil), might co-exist in rice field.…”
Section: Resultsmentioning
confidence: 99%